Increased mutagenesis mediated by cloned plasmid CAM-OCT genes: potential for expanding substrate ranges of Pseudomonas spp. - McBeth, D L (1996)
Twenty-five kilobases of Pseudomonas plasmid CAM-OCT DNA encoding a DNA repair gene(s) was cloned into the broad-host-range vector pVK100. The presence of the cloned genes increased the isolation frequency of Pseudomonas putida derivatives capable of using ethyl lactate or 3-methyl-3-buten-1-ol as their carbon source 15- and 8-fold, respectively, after UV irradiation. Ethyl lactate-utilizing strains expressed a novel intracellular hydrolase.